The Analysis of Motivation and Mathematics Learning Interest of Students in Madrasah Tsanawiyah - Pamungkas, Cucuk Tri; Baiduri, Baiduri; Inganah, Siti (MEJ (Mathematics Education Journal), 2018)
This research is aimed to describe about motivation and mathematics learninginterest of students in Madrasah Tsanawiyah. The type of this research isdescriptive research with quantitative and qualitative approaches. The sampleof this research is 49 students of class VII, 60 students of class VIII, and 47students of class IX. The researcher used questionnaires in this research as thedata collection techniques. Based on the obtained analysis, the averageindicator of motivation to learn mathematics that include: facing the taskdiligently for about 2,8 is categorized as fairly well, interesting learningactivities of 3,22 is categorized good, encouragement, needs andappreciations of learning have the same average that is equal to 2,7 iscategorized fairly well, the conducive learning environment of 2,58 iscategorized fairly well, with students’ average motivation to learnmathematics in Madrasah Tsanawiyah for about 2,8 and categorized fairlywell. The average indicator of interest in mathematics learning whichincludes: attention in learning mathematics of 3,11 is categorized good, theexcitement in learning mathematics equal to 3,04 is categorized good, theinterest in learning mathematics equal to 2,71 is categorized as fairly well,with the average of students’ learning interest in mathematics of MadrasahTsanawiyah for about 2,95 and categorized as fairly well